The Future of Professional Forestry Education: Trends and Challenges from the Malaysian Perspective - Jegatheswaran RATNASINGAM; Florin IORAS; Claudia Cristina VACALIE; Lu WENMING (Notulae Botanicae Horti Agrobotanici Cluj-Napoca, 2013)
The traditional forestry education schemes are no longer sufficient to train professional foresters to manage the forest resources in a changing world. Even in forest-rich nations such as Malaysia, the challenges faced by forestry education are growing. The declining student enrolment and interests in the field must be stopped, if the field is to remain viable. The roles played by the forest have shifted from purely commercial products exploitation to environmental and social centric. In this context, forestry education will need to be restructured to impart the necessary knowledge and skills to the foresters to enable them to perform up to expectation in the field.